Principle of Independence in Construction Service Contracts - Japar, Sugiarto Raharjo (Global Writing Academica Researching & Publishing, 2025)
This paper examines the pivotal role of the engineer's independence and impartiality in the administration of construction contracts. Adopting a normative approach, the study analyzes the contractual provisions and legal principles governing the engineer's independence, as well as the application of this concept across different legal systems. The findings suggest that while the notion of the engineer as an independent and unbiased party is well-established in certain jurisdictions, particularly those utilizing FIDIC contracts, it is less familiar in civil law systems, where the contract administrator is often perceived as representing the employer's interests. The paper emphasizes the critical significance of preserving the engineer's independence to ensure fairness, transparency, and effective dispute resolution in the construction industry. Maintaining the engineer's independence is essential for upholding the integrity and fairness of the construction contract administration process, enabling objective decision-making without undue influence from the employer or other project stakeholders.